The Effect of Apis dorsata Honey Treatment on Calcium Levels of Mandibular Bone in Ovariohysterectomized Wistar Rats - Rohmah, Siti Nur; Yudaniayanti, Ira Sari; Primarizky, Hardany; Hastutiek, Poedji (Jurnal Medik Veteriner, 2023)
This study aimed to evaluate the efficacy of Apis dorsata honey on calcium levels in the mandibular bone of Wistar rats after ovariohysterectomy as an animal osteoporosis model for treating cases of osteoporosis. This study used 20 female rats, which were divided into five treatment groups with four replications. SHAM was the negative control group; OH was the ovariohysterectomized group without treatment as a positive control; the AD1, AD2, and AD3 groups were ovariohysterectomized rats with A. dorsata honey at doses of 1 g/kg bw, 2 g/kg bw, and 4 g/kg bw for 84 days. After 84 days of treatment, the left mandibular bones of the rats were collected, weighed, and stored in 10% neutral buffered formalin. Calcium levels were calculated using proximate analysis. The results showed a decrease in bone calcium levels in the ovariohysterectomy group, the highest results were in the SHAM group, and the lowest results were in the AD3 group. It can be concluded that the administration of A. dorsata honey could not maintain the calcium level of the mandibular bone in the ovariohysterectomized Wistar rats.